Estudos morfo-anatômicos de acrocomia aculeata (jacq.) lodd. ex mart. (arecaceae). - Ramos, Wendell de Jesus Lobo (Museu Paraense Emílio Goeldi, 2023)
Palm trees are widely distributed in the Neotropics with up to 3,500 species in about 240 genera, highlighting among these, Acrocomia aculeata (Jacq.) Lodd. Ex Mart, widely spread throughout the Brazilian territory, with various uses such as providing wood for rural construction, textile fibers for nets and fishing lines, edible fat, and great potential for landscaping. The objective of this study is to characterize the species morpho-anatomically. The botanical material was collected at the Zoobotanical Park of the Emílio Goeldi Museum of Pará (MPEG), herborized and incorporated into the João Murça Pires Herbarium (MG 170231) and submitted to the usual techniques of plant anatomy. The species has a straight, solitary stem of 10 to 15m, covered with fine spines except on the branches and fruits; the drupes have a hard, cream-colored epicarp. The leaf surface of the adaxial face in the costal region presents cells of various shapes and sizes arranged mostly longitudinally in relation to the venations while the intercostal region presents isodiametric, hexagonal cells arranged diagonally in relation to them. On the abaxial face between the epidermal cells are tetracyclic stomas, whose subsidiary cells are alter-shaped, filiform and pluricellular trichomes. In the mesophyll region it can be seen that it is dorsiventral, with 2 to 3 layers of paliçadic parenchyma while the lacunose parenchyma is reduced with small intercellular spaces. Many of these characteristics are common to the genus Acrocomia, but there are specific characteristics to the taxon under study, such as a silica crown around the fibers and biseriate parenchyma.